مسؤولية أعوان المحاسبة العمومية في مجال الصفقات العمومية - بن شايب ، دويم; بونقاب ، السعيد (جامعة الوادي University of El Oued, 2025)
العقود العمومية هي نفقات عمومية تهدف إلى تحقيق المصلحة العامة وتلبية احتياجات المتعهد العمومي، وتخضع لقانون المحاسبة العمومية والإدارة المالية، في إطار ميزانية محددة. ويُنفذ هذه الميزانية، من ناحيتي الإيرادات والنفقات، من قِبل محاسبين عموميين، وفقًا للصلاحيات المحددة في القانون 23-07، المتضمن قواعد المحاسبة العمومية والإدارة المالية، والمراسيم التنفيذية الصادرة بموجبه. وهذا يضمن مبدأ فصل الصلاحيات بين المفوض، والمحاسب العمومي، ومراقب الميزانية، من خلال تحديد المهام وتقسيمها بما يحقق الاستخدام الأمثل للموارد المالية العمومية، وفقًا لبرامج تُنفذ، لا سيما من خلال العقود الإدارية في شكل عقود عمومية. وفي إطار إعداد هذه العقود وإبرامها وتنفيذها ومراقبتها، لا بد من التطرق إلى مسؤولية المحاسبين العموميين في مجال العقود العامة، سواء كانت مدنية نتيجة خطأ أو إهمال، أو مالية تتعلق بالتسبب في ضرر للخزينة العامة، أو جنائية لمخالفة قاعدة جزائية. Public contracts are public expenditures whose purpose is to achieve the public interest and meet the needs of the public operator subject to the Public Accounting and Financial Management Law within the framework of a specific budget. This budget is implemented on both the revenue and expenditure sides by public accounting officers in accordance with the powers defined by Law 23-07, containing the rules of public accounting and financial management and the executive decrees issued pursuant to it. This guarantees the principle of separation of powers between the authorizing officer, the public accountant, and the budget controller by defining and dividing tasks to achieve the best use of public financial resources according to programs implemented in particular through administrative contracts in the form of public contracts. Within the framework of preparing, concluding, implementing, and monitoring these contracts, it is necessary to address the responsibility of public accounting officers in the field of public contracts, whether civil as a result of error or negligence, financial related to causing harm to the public treasury, or criminal for breach of a penal rule.
Keywords: مسؤولية ،أعوان، المحاسبة العمومية ، الصفقات العمومية; Responsibility; agents; public accounting; public procurement